Cost-Free Policy and the Pursuit of Quality Education: An Exploratory Study in Islamic Secondary Education - Muhtadin (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study explores the implementation of cost-free education policies in Islamic secondary schools, with a focus on how such policies contribute to the pursuit of quality education. Rooted in the national initiative to improve educational access and equity, the research specifically examines the management of School Operational Assistance (Bantuan Operasional Sekolah/ BOS) funds in a religious education setting. Using a qualitative exploratory design, data were gathered through observations, in-depth interviews, and document analysis. Findings reveal that BOS fund management is marked by participatory planning, accountable execution, and digital-based transparency. The leadership of school principals proves instrumental in aligning budget use with educational priorities and stakeholder engagement. Despite limited funding, these mechanisms have led to notable improvements in educational service delivery. The study contributes to the discourse on educational policy by highlighting the role of governance and community involvement in maximizing the impact of cost-free education initiatives. Penelitian ini mengeksplorasi implementasi kebijakan pendidikan tanpa biaya pada jenjang pendidikan menengah Islam, dengan fokus pada kontribusi kebijakan tersebut terhadap peningkatan mutu pendidikan. Kebijakan ini merupakan bagian dari inisiatif nasional untuk memperluas akses dan pemerataan pendidikan, yang dalam konteks ini dikaji melalui pengelolaan dana Bantuan Operasional Sekolah (BOS) di lingkungan pendidikan keagamaan. Dengan menggunakan desain eksploratif kualitatif, data dikumpulkan melalui observasi, wawancara mendalam, dan studi dokumentasi. Temuan menunjukkan bahwa pengelolaan dana BOS dilakukan melalui perencanaan partisipatif, pelaksanaan yang akuntabel, dan transparansi berbasis digital. Kepemimpinan kepala madrasah memainkan peran kunci dalam menyelaraskan penggunaan anggaran dengan prioritas pendidikan serta membangun keterlibatan para pemangku kepentingan. Meskipun dana terbatas, mekanisme ini terbukti mampu meningkatkan kualitas layanan pendidikan. Studi ini memberikan kontribusi pada wacana kebijakan pendidikan dengan menekankan pentingnya tata kelola dan partisipasi masyarakat dalam mengoptimalkan dampak dari kebijakan pendidikan tanpa biaya.